Design of collaborative studies to assess the impact of diseases on production: Case study of trypanosomiasis in peri-urban dairy production systems in Uganda - Patzelt, R.J.; Schares, G.; Peregrine, A.S.; Lessard, P.; Laker, C.; Leak, S.G.A.; Mehlitz, D. (German Foundation for International Development, 1996)
The peri-urban dairy production systems in Uganda, located in the subhumid agro-ecological zone with medium rainfall have a high potential for livestock production (Walsche et al., 1991; Winrock, 1992), but medium tsetse challenge and the associated trypanosomiasis risk may adversely affect dairy production. Thus, the Institute for Parasitology and tropical Veterinary Medicine of the Free University of Berlin (FUB), Germany with it's Collaborative Research Unit (C.R.U.), Entebbe, Uganda has initiated a collaborative research project in co-operation with the International Livestock Research Institute (ILRI) and the National Agricultural Research Organisation (NARO), Uganda, to conduct applied field and laboratory based research to assess the impact of trypanosomiasis on the peri-urban dairy production systems in Uganda. The study quantifies the prevalence of animal trypanosome infections, helminth infections and tick borne diseases in the observed production system, describes the infection dynamics of trypanosome and helminth infections, assesses the risk factors for trypanosomiasis and the influence of trypanosomiasis, helminth infections and tick borne diseases on productivity of dairy herds in the observed system.